2021
DOI: 10.1039/d1nj00170a
|View full text |Cite
|
Sign up to set email alerts
|

High-energetic and low-sensitive 1,3,5-triamino 2,4,6-trinitrobenzene (TATB) crystal: first principles investigation and Hirshfeld surface analysis

Abstract: First principles investigations and Hirshfeld surface analysis of 1,3,5-triamino 2,4,6-trinitrobenzene (TATB) crystal have been carried out. The geometrical and electronic structures of TATB molecules in the crystal and gas phase...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Furthermore, from the X-ray diffraction data, it can be found that the bond lengths of the C–NO 2 bond in ZDPT and those in reference explosives were about 1.40 Å for ZDPT , 1.42 Å for TATB, and 1.459 Å for TNDPT (Table S5†). 54,60 From these values, it is clear that ZDPT has the shortest C–NO 2 bond length, which could explain its high thermal stability.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, from the X-ray diffraction data, it can be found that the bond lengths of the C–NO 2 bond in ZDPT and those in reference explosives were about 1.40 Å for ZDPT , 1.42 Å for TATB, and 1.459 Å for TNDPT (Table S5†). 54,60 From these values, it is clear that ZDPT has the shortest C–NO 2 bond length, which could explain its high thermal stability.…”
Section: Resultsmentioning
confidence: 96%
“…The high explosive 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) is exceptionally insensitive to accidental thermal and shock initiation, making it widely applicable for both defense and civilian purposes . The unexpected insensitivity of TATB has been attributed to strong hydrogen bonding, , π-stacking interactions, and cooperativity between these phenomena . In particular, the intramolecular hydrogen bonding between the ortho nitro and amino groups in the TATB molecule contributes to its stability to thermal bond dissociation .…”
Section: Introductionmentioning
confidence: 99%
“… 1 The unexpected insensitivity of TATB has been attributed to strong hydrogen bonding, 2 , 3 π-stacking interactions, 4 and cooperativity between these phenomena. 5 In particular, the intramolecular hydrogen bonding between the ortho nitro and amino groups in the TATB molecule contributes to its stability to thermal bond dissociation. 6 Excitation with UV light, in contrast, has long been known to induce photochemical reactions in TATB.…”
Section: Introductionmentioning
confidence: 99%
“…There are other crystallographic studies reporting O•••O interactions but they only support their findings on a few topological parameters. [11][12][13] Furthermore, when oxygen is bonded to some electronwithdrawing fragments (like fluorine, in OF 2 ) it can form an O-centered chalcogen-bonding interaction with several Lewis bases. [14][15][16] The interaction energy of these type of complexes is originated not only from the primary chalcogen, but also from the contribution of other secondary interactions.…”
Section: Introductionmentioning
confidence: 99%